Measuring individual-level needle and syringe coverage among people who inject drugs in Myanmar - O’Keefe, Daniel; Aung, Soe Moe; Pasricha, Naanki; Wun, Thu; Linn, Soe Khaing; Lin, Nay; Aitken, Campbell; Hughes, Chad; Dietze, Paul (The International journal of drug policy, 2018)
Myanmar has prioritised people who inject drugs (PWID) as a key population for HIV mitigation efforts, with targets for needle and syringe distribution set at a population level. However, individual-level coverage, defined as the percentage of an individual’s injecting episodes covered by a sterile syringe, is a more sensitive measure of intervention coverage. We sought to examine individual-level coverage in a sample of PWID in Myanmar. We recruited 512 PWID through urban drop-in-centres in Yangon, Mandalay and Pyin Oo Lwin. Participants were administered a quantitative questionnaire covering five domains: demographics, drug use, treatment and coverage, and injecting risk behaviour. We calculated past fortnight individual-level syringe coverage, estimating levels of sufficient (≥100% of injecting episodes covered by a sterile syringe) and insufficient (<100%) coverage, and examined associations between key variables and insufficient coverage via logistic regression. Our sample was predominately male (97%), employed (76%), and living in stable accommodation (96%), with a median age of 27. All participants reported heroin as the drug most frequently injected, and injected a median of 27 times in the past two weeks. Nineteen per cent of participants had insufficient coverage in the two weeks before interview. Insufficient coverage was positively associated with syringe re-use (AOR: 5.19, 95% CIs: 2.57, 10.48) and acquiring sterile syringes from a location other than a formal drop-in-centre (AOR: 2.04, 95% CIs: 1.08, 3.82). Participants recruited in Mandalay (AOR: 0.30, 95% CIs: 0.11, 0.80) and Pyin Oo Lwin (AOR: 0.39, 95% CIs: 0.18, 0.87) had lower odds of insufficient coverage than those recruited in Yangon. Our study shows coverage in selected areas of Myanmar was comparable with studies in other countries. Our results inform the delivery of harm reduction services for PWID, specifically by encouraging the use of formal drop-in-centres, over other sources of syringe distribution, such as pharmacies.